The Influence of Microwave Sterilization on the Ultrastructure, Permeability of Cell Membrane and Expression of Proteins of Bacillus Cereus - Cao, Jin-Xuan; Wang, Fang; Li, Xuan; Sun, Yang-Ying; Wang, Ying; Ou, Chang-Rong; Shao, Xing-Feng; Pan, Dao-Dong; Wang, Dao-Ying (Frontiers in Microbiology, 2018)
Bacillus cereus was isolated from ready-to-serve brine goose, identified by 16S rRNA gene sequencing analysis and treated with the microwave power of 1800 W at 85 oC for 5 min. The influence of microwaves on the morphology, the permeability of membrane and the expression of total bacterial proteins was observed. Microwave induced the clean of bacterial nuclear chromatin, increased the permeability and disrupted the integrity of membrane. Twenty-three proteins including 18 expressed down-regulated proteins and 5 expressed up-regulated proteins were identified by HPLC-MS/MS in the samples treated with microwave. The frequencies of proteins changed after microwaves treatment were labeled as 39.13% (synthesis and metabolism of amino acid or proteins), 21.74% (carbohydrate metabolism), 8.70% (anti-oxidant & acetyl Co-A synthesis), and 4.35% (the catalyst of catabolism of bacterial acetoin, ethanol metabolism, glyoxylate pathway, butyrate synthesis and detoxification activity), respectively. This study indicates that microwaves result in the inactivation of Bacillus cereus by cleaning nuclear chromatin, disrupting cell membrane and disordering the expression of proteins.